Perencanaan Tangki Reservoir Distribusi Air Bersih Untuk Bangunan Tiga Lantai Kapasitas 11000 Liter - Safarno, Safarno; Gunawan, Yuspian; Aksar, Prinob (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2023)
The tank is a place to store water and so on, when designing many aspects that need to be considered so that a good and efficient tank design is obtained. The purpose of this study was to determine the parameters of the tank design, rolling process, suitable welding and service life of the reservoir tank capacity of 11000 liters with ASTM 304 material. The method in this study was to plan a reservoir tank capacity of 11000 liters, then calculate the strength analysis on the tank used planned, calculating the service life and efficiency of tank use. The results of this study indicate that the tank pressure is 0.0035 kg/mm2, the allowable stress is 2.11kg/mm2, the thickness of the shell plate is 6.5 mm, the bottom plate is 8 mm, the roof plate is 6 mm, the circumferential stress is 0.53 kg/mm2, longitudinal stress 0.26 kg/mm2. The length of the plate rolling was 393.31 mm, the rolling force was 1090.82 kg, the plate roll strength was 25.34 kg/mm2. In welding, the previous tie weld will be carried out with a length of 60 mm and a distance between the welds of 200 mm. The estimated age of the tank is obtained by the use of the tank for approximately 87 years.Keywords: Tank, Rolling, welding.